Lava flow hazard and risk at Mt. Cameroon volcano - Favalli, Massimiliano; Tarquini, Simone; Papale, Paolo; Fornaciai, Alessandro; Boschi, Enzo (Bulletin of volcanology, 2012)
Mt. Cameroon is one of the most active effusive volcanoes in Africa. About 500,000 people living or working around its fertile flanks are subject to significant threat from lava flow inundation. Lava flow hazard and risk were assessed by simulating probable lava flow paths using the DOWNFLOW code. The vent opening probability density function and lava flow length distribution were determined on the basis of available data from past eruptions at Mt. Cameroon volcano. Code calibration was performed through comparison with real lava flow paths. The topographic basis for simulations was the 90-m resolution SRTM DEM. Simulated lava flows from about 80,000 possible vents were used to produce a detailed lava flow hazard map. The lava flow risk in the area was mapped by combining the hazard map with digitized infrastructures (i.e., human settlements and roads). Results show that the risk of lava flow inundation is greatest in the most inhabited coastal areas comprising the town of Limbe, which constitutes the center of Cameroon’s oil industry and an important commercial port. Buea, the second most important town in the area, has a much lower risk although it is significantly closer to the summit of the volcano. Non-negligible risk characterizes many villages and most roads in the area surrounding the volcano. In addition to the conventional risk mapping described above, we also present (1) two reversed risk maps (one for buildings and one for roads), where each point on the volcano is classified according to the total damage expected as a consequence of vent opening at that point; (2) maps of the lava catchments for the two main towns of Limbe and Buea, illustrating the expected damage upon venting at any point in the catchment basin. The hazard and risk maps provided here represent valuable tools for both medium/long-term land-use planning and real-time volcanic risk management and decision making.